Using SWOT Analysis to Design Organizational Structure in Small Enterprise - Litasari Widyastuti Suwarsono; Atya Nur Aisha; Dwi Wahyuni; Fida Nirmala Nugraha (Program MM Universitas Surabaya, 2022)
One of the biggest challenges of MSMEs is how to manage its resources to increase their business. Ani's Craft, already survives for 6 years now faces challenges to growth because lack of strategic planning, ineffective of HR management and unstructured organizational design. This study aims to design an organizational structure based on strategy that will help the small enterprise to growth. The study began with identifying the internal and external factors that influence its business. Result shows the strategy that fits the conditions was the WO strategy. New organizational structure was proposed that emphasize the importance of company's needs by adding marketing and finance divisions.